Timing of systemic resistance induced by local exogenous ABA application within clonal network of stoloniferous herb Centella asiatica subjected to low water availability - Duan, Su-Juan; Sun, Gui-Jia; Dan, Yi; Deng, Jie; Yu, Dong-Wei; Wei, Qin; Chen, Chang-Fan; Jiang, Jie; Wang, Xue-Mei; Ren, Ting-Ju; Liao, Yong-Mei; Chen, Jin-Song (Frontiers in Plant Science, 2024)
Resistance traits of plants can be activated both at the damaged site and undamaged parts.Systemic resistance induced by local exogenous abscisic acid (ABA) application alleviated negative effect of low water availability on growth performance of clonal plant. However, timing of systemic resistance was poorly understood. Timing of systemic resistance refers to its activation and decay time within clonal network. Clonal fragment of Centella asiatica with four successive ramets (including first-oldest, second-older, third-old and fourth-young ramets) subjected to low water availability (20% soil moisture content) was used to explore effects of local exogenous ABA application on the timing of resistance activation and decay. Systemic resistance activated by local exogenous ABA application after 4 days remained at least 28 days.Compared with control, biomass accumulation of whole clonal fragment, root biomass and ratio of belowground to aboveground biomass significantly increased by local exogenous ABA application after 28 days. It is suggested that rapid activation and delay of resistance response induced by local exogenous ABA application within clonal network may improve fitness of clonal plant subjected to abiotic stress.